Receptiveness and Challenges to use Learning Management System among Social Studies Undergraduates in Kwara State - YAYI, Timothy Opeyemi (Ilorin Journal of Education, 2023)
Education and learning have been improved by Learning Management System through the integration of many technologies used for educational purposes such as computers, the internet, and mobile technologies. Outbreak of Covid 19 have disrupted academic calendar in which efficient use of Learning Management System could have been solved. The study investigated the receptiveness to use LMS among Social Studies students in Kwara State. The study adopted a descriptive survey research design method. The population of the study was made up of all Social Studies undergraduates in Kwara State. Purposive sampling technique was used for the purpose of the study. Self-structured questionnaire which was validated by two experts in Social Studies was used as instrument for the study. A reliability co-efficient of 0.81 was also derived after a test retest. Data were analyzed using descriptive statistics of frequency, percentage and mean rating. The study showed that sampled undergraduates are receptive to Learning Management System. This means that receptiveness of learning management system was positive and difficulty of LMS coordination was the major challenge. Based on the findings of the study it was recommended that the undergraduates and instructors should be encouraged to continue using the Learning Management System by the authority of the institution.